2020
DOI: 10.3233/wor-203173
|View full text |Cite
|
Sign up to set email alerts
|

Research update: The relation between ME/CFS disease burden and research funding in the USA

Abstract: BACKGROUND: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a debilitating, chronic, multisystem disease that affects an estimated 1 to 2.5 million Americans. It has no widely accepted biomarkers and no FDA-approved treatment. ME/CFS has traditionally been one of the lowest funded diseases by the United States National Institutes of Health (NIH). OBJECTIVES: We provide here an update to our 2016 article, which estimated the disease burden of ME/CFS in the United States in 2013 and its relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 13 publications
0
32
0
1
Order By: Relevance
“…Listed with each disease is the ratio of actual funding to that commensurate with disease burden for years 2015, 2017, and 2019 (based on the regression curve for the corresponding year). Also included 4 Reprinted with permission from IOS Press.) are 2015 burden in DALY (millions) and 2019 funding (millions of dollars, obtained from RCDC funding source).…”
Section: Funding Versus Gender Prevalencementioning
confidence: 99%
“…Listed with each disease is the ratio of actual funding to that commensurate with disease burden for years 2015, 2017, and 2019 (based on the regression curve for the corresponding year). Also included 4 Reprinted with permission from IOS Press.) are 2015 burden in DALY (millions) and 2019 funding (millions of dollars, obtained from RCDC funding source).…”
Section: Funding Versus Gender Prevalencementioning
confidence: 99%
“…However, in terms of undertaking such research, it is important to note that the relatively small amount of existing research on ME/CFS is in part a result of the lack of funding available in this field/area. For example, it has been shown that ME/CFS is more underfunded with respect to burden than any other disease in the US, with the illness receiving roughly 7% of that commensurate with disease burden 51 . To date, there has been very limited research on ME/ CFS in Ireland and this is something that should be urgently addressed.…”
Section: Resultsmentioning
confidence: 99%
“…These deficiencies are directly related to the extremely low level of research funding for ME/CFS in the US [29] and worldwide [30]. In the US, ME/CFS research is underfunded by about a factor of 14 relative to its burden of disease [31,32]. One reason for this may be that pwME are predominantly female, and, as recently demonstrated in Mirin (2020) [33], female-dominated diseases tend to be underfunded relative to male-dominated diseases.…”
Section: Discussionmentioning
confidence: 99%